2019
DOI: 10.1016/j.mjafi.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Level of work stress and factors associated with bruxism in the military crew of the Peruvian Air Force

Abstract: Background: Military life leads to a great personal sacrifice and labor in the aircrew because they are constantly subjected to innumerable activities which have a great work pressure; therefore, the aim of this study was to determine the level of work stress associated with bruxism in the aircrew of the Peruvian Air Force. Methods: This was a cross-sectional study. A total of 204 crew members of the Peruvian Air Force from the Air Group were surveyed, and the stomatological clinical inspection was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 14 publications
0
18
0
3
Order By: Relevance
“…Ten analytical cross‐sectional studies were included. They were published in Brazil, 41‐43 Greece, 24 Indonesia, 44 Turkey, 45 Lithuania, 46 Peru, 47 Poland 48 and the United States 49 . They were published between 1980 and 2020.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten analytical cross‐sectional studies were included. They were published in Brazil, 41‐43 Greece, 24 Indonesia, 44 Turkey, 45 Lithuania, 46 Peru, 47 Poland 48 and the United States 49 . They were published between 1980 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…The largest sample presented was 394 42 individuals and the smallest, 30 49 . In addition, only two of the included studies reported a priori calculations to estimate sample size 46,47 . Only three studies could be included for quantitative analysis 24,46,48 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…e time and speed of ossification are primarily affected by the socioeconomic development of the Peruvian population. In this way, in the future, it will prevent the appearance of bruxism and other parafunctions of the temporomandibular joint [29]. Of all the studies and procedures used for the evaluation of the stages of bone maturation and dental mineralization, the ones that have reached the most diffusion have been the qualitativedescriptive methods; this general method has the purpose of predicting and establishing the moment specific to the different states or events of sudden pubertal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, translucency may be maintained by the thirds most resistant to direct dissolution. [ 7 8 9 10 11 ]…”
Section: Introductionmentioning
confidence: 99%